Financial intelligence : a manager's guide to knowing what the numbers really mean - Berman, Karen , 1962-; Case, John , 1944-; Knight, Joe , 1963- (Harvard Business School Press, 2006)
Karen Berman and Joe Knight teach the basics of finance--but with a twist. Accountants rely on estimates, assumptions, and judgment calls. Savvy managers need to know how those sources of possible bias can affect the financials and that sometimes the numbers can be challenged. While providing the foundation for a deep understanding of the financial side of business, the book also arms managers with practical strategies for improving their companies' performance. --from publisher description